Impact of inter-core crosstalk on the performance of multi-core fibers-based SDM systems with coherent detection - Pinheiro, B. R. P. (2019)
Inter-core crosstalk (ICXT) can limit the multi-core fiber (MCF) systems performance and transmission reach. Over the last years, the impact of the ICXT on the performance of MCF optical communication systems with coherent detection has been investigated in several works. However, the influence of the MCF parameters and transmitted signal characteristics on the ICXT mechanism and the degradation induced by it on the performance of coherent detection MCF systems are still to be completely assessed. In this work, the impact of the ICXT on the performance of coherent detection MCF-based transmission systems is assessed through numerical simulation considering fiber linear propagation. The metrics used to assess the MCF system performance are the bit error rate (BER) and the optical signal-to-noise ratio (OSNR) penalty due to the ICXT. Our results show that the BER and the OSNR penalty due to the detected ICXT, in MCF-based systems with coherent detection, are influenced by the s kew, time misalignment between the transmitted signals and the roll-off factor of the transmitted signals. In the range of skew and roll-off factors analyzed, the maximum reduction of maximum ICXT level for a 1 dB OSNR penalty by appropriate choice of skew and roll-off factor does not exceed 1.7 dB.